PENERAPAN MODEL PEMBELAJARAN PAIR-CHECKS TERHADAP HASIL BELAJAR IPAS SISWA KELAS V SD NEGERI 35 LUBUKLINGGAU - Selvi; Ahmad Gawdy Prananosa; Aren Frima (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of applying the Pair-Checks learning model on IPAS learning outcomes of Grade V students at SD Negeri 35 Lubuklinggau in the 2025/2026 academic year. The research method used was quantitative with a pre-experimental design of the one group pretest-posttest type. Based on data analysis, the average pretest score of students was 45.39, with most students not yet achieving learning mastery. After applying the Pair-Checks learning model, the average posttest score increased to 83.09, with 21 out of 23 students achieving mastery learning. Hypothesis testing using the Z-test showed Zhitung ≥ Ztabel (6.85 ≥ 1.714), indicating that H₀ was rejected and Hₐ was accepted. Thus, it can be concluded that the implementation of the Pair-Checks learning model significantly improved the IPAS learning outcomes of Grade V students at SD Negeri 35 Lubuklinggau.